Arboreal insects and mangrove vegetation pollinators in Bunaken National Park, North Sulawesi, Indonesia - RONI KONERI; PARLUHUTAN SIAHAAN; SAROYO SAROYO; MEIS JACINTA NANGOY; WAKHID WAKHID (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Koneri R, Siahaan P, Saroyo, Nangoy MJ, Wakhid. 2025. Arboreal insects and mangrove vegetation pollinators in Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 26: 1553-1564. The diversity of mangrove species is predominantly composed of animals and plants, where insects have not been fully explored. Therefore, this study aimed to analyze the diversity of arboreal insects and mangrove vegetation pollinators on the Coast of Bunaken Sub-district, Manado City, North Sulawesi, Indonesia. Sampling was conducted at 3 observation stations in mangrove vegetation using the beating-tray method to obtain arboreal insects. Scan sampling and insect nets were used for mangrove vegetation pollinators. The results showed that arboreal insects and mangrove vegetation pollinators comprised 1,028 individuals covering 45 species in 17 families and 6 orders. The order with the highest abundance was Hymenoptera, while the largest number of species was Lepidoptera. Based on the relative abundance of species, Oecophylla smaragdina, Tetrigona apicalis, and Dolichoderus thoracicus were ranked as 1, 2, and 3, respectively. The average index of dominance, richness, and diversity of arboreal insects and the highest mangrove vegetation pollinators were found at Meras station. The similarity analysis indicated that the composition of arboreal insects and mangrove vegetation pollinators did not show significant differences. Environmental factors such as air temperature, air humidity, wind speed, and light intensity at the 3 observation stations were different. The highest air temperature and wind speed were found at the Tongkaina, while Meras had the lowest. The common species distribution pattern found was aggregate, suggesting that the mangrove vegetation area on the coast of Bunaken could support the abundance, richness, and diversity of arboreal insects as well as mangrove vegetation pollinators. At all observation stations, approximately the same species of insect composition was found. These results provided valuable information, serving as a database and consideration in formulating conservation strategies for arboreal insects and mangrove vegetation pollinators in the mangrove forest area on the Coast of Bunaken Sub-district.